Reflexões sobre a concordância verbal com alguns pronomes-sujeito em português - Gomes, Alexandro Teixeira (2002)
This article is made up of partial results related to a research project The Verbal Agreement in the Fortaleza Oral Standard Portuguese, whose data are based on the PORCUFORT. The results here are limited to the verbal agreement with subject pronouns tu, a gente, eles. As to the first one, I verify to what extent the standard agreement occurs; as to the second, I verify whether there is a formal or semantic agreement. Concerning the third, I examine whether the agreement is the regular one established by traditional grammars or not. I go beyond the sheer data explaining and analyzing them.